Factors related to falls in active women over 50 years old: associated clinical and functional aspects Abstract - Ferreira Moreira, Mariana; de Melo Barbosa, Aurélio; Leite Orcino, Juliane; Estevam Brom Vieira, Martina; Callais Franco do Nascimento, Tauana; Augusto Santos Bueno, Guilherme; Martins Gervásio, Flávia (O Mundo da Saúde, 2020)
Falling is a public health problem as it results in physical, psychosocial and economic damage. Identifying factors related to the risk of falling in a given population allows for the development of more specific preventive activities. The objective of this study was to associate clinical and functional characteristics with the recent history of falls in middle-aged and elderly women. A total of 152 physically active women participated in the study, 50 of whom have reported one or more falls in the last twelve months. Self-reported clinical comorbidities and motor functionality were verified using the 30’’ Chair Stand Test (30CST) and the Balance Evaluation System Test (BESTest). Spearman correlation and a logistic regression analysis with the forward stepwise method were applied, considering p≤0.05. Age was inversely correlated with all BESTest items. Independent variables that were predictors of past falls were: number of comorbidities (p=0.017), performing 8 repetitions or less in the 30CST (p=0.036), having a score of 86.7% (13 points) or less in BESTest I (p=0.038), with a score of 73.3% (11 points) or less in BESTest V (p=0.050). There was an association between a history of falls and changes in muscle strength of the lower limbs and postural balance, related to biomechanical restrictions and sensory orientation in women in the study’s age group. It is concluded that, women over 50 years old, physically active, with a history of falls, demonstrate that the number of comorbidities and the lower motor performance are factors associated with the risk of falling.